Receptor activity-modifying protein modulation of parathyroid hormone-1 receptor function and signaling - Avgoustou, Paris; Jailani, Ameera B. A.; Desai, Aditya J.; Roberts, David J.; Lilley, Ewan R.; Stothard, Grant W.; Skerry, Timothy M.; Richards, Gareth O. (Frontiers in Pharmacology, 2024)
Introduction Receptor activity-modifying proteins (RAMPs) are known to modulate the pharmacology and function of several G-protein-coupled receptors (GPCRs), including the parathyroid hormone 1 receptor (PTH1R). However, the precise effects of different RAMPs on PTH1R signalling and trafficking remain poorly understood. This study investigated the impact of RAMP2 and RAMP3 on PTH1R function using a range of PTH and PTH-related protein (PTHrP)-derived ligands. Methods We employed FRET imaging to assess PTH1R interactions with RAMPs. Cell surface expression of PTH1R was evaluated in the presence of RAMPs. PTH1R-mediated cAMP accumulation, β-arrestin recruitment, and calcium signalling were measured in response to various ligands. Antibody-capture scintillation proximity assays were used to examine G-protein activation patterns. Results PTH1R preferentially interacted with RAMP2 and, to a lesser extent, RAMP3, but not with RAMP1. RAMP3 co-expression reduced cell surface expression of PTH1R. RAMP2 significantly enhanced PTH1R-mediated signalling responses to PTH (1-34), PTHrP (1-34), PTH (1-84), and PTH (1-17) analogue ZP2307, while RAMP3 co-expression attenuated or abolished these responses. Full-length PTHrP analogues exhibited lower potency and efficacy than PTHrP (1-34) in activating PTH1R. RAMP2 increased the potency and/or efficacy of these analogues, whereas RAMP3 reduced these responses. RAMP2 differentially modulated G-protein activation by PTH1R in a ligand-dependent manner, with PTH (1-34) and PTHrP (1-34) inducing distinct patterns of G-protein subtype activation. Discussion These findings highlight the complex role of RAMPs in regulating PTH1R signalling and trafficking, revealing differential effects of RAMP2 and RAMP3 on receptor function. The data suggest that targeting the PTH1R/RAMP2 complex may be a promising strategy for developing novel bone anabolic therapies by leveraging biased agonism and functional selectivity. Further research using physiologically relevant models is needed to elucidate the therapeutic potential of this approach.